On Regularity of Certain Linear Expansions of Dynamical Systems on a Torus - Kulik, V. L.; Stepanenko, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We investigate the problem of the existence of the Green–Samoilenko function for linear expansions of dynamical systems on a torus of the form dφ dt = a(φ ), C(φ )dφ dt + 12C(φ )x = A(φ )x, where C(ϕ) ∈ C′(T m; a) is a nondegenerate symmetric matrix.